What Is Meditation? Proposing an Empirically Derived Classification System - Matko, Karin; Sedlmeier, Peter (Frontiers in Psychology, 2019)
Meditation is an umbrella term, which subsumes a huge number of diverse practices. It is still unclear how these practices can be classified in a reasonable way. Earlier proposals have struggled to do justice to the diversity of meditation techniques. To help in solving this issue, we used a novel bottom-up procedure to develop a comprehensive classification system for meditation techniques. In previous studies, we reduced 309 initially identified techniques to the 20 most popular ones. In the present study, 100 experienced meditators were asked to rate the similarity of the selected 20 techniques. Using multidimensional scaling, we found two orthogonal dimensions along which meditation techniques could be classified: activation and amount of body orientation. These dimensions emphasize the role of embodied cognition in meditation. Within these two dimensions, seven main clusters emerged: mindful observation, body-centered meditation, visual concentration, contemplation, affect-centered meditation, mantra meditation, and meditation with movement. We conclude there is no “meditation” as such, but there are rather different groups of techniques that might exert diverse effects. These groups call into question the common division into “focused attention” and “open-monitoring” practices. We propose a new embodied classification system and encourage researchers to evaluate this classification system through comparative studies.